Proceedings of the workshop Workshop Strategies for Strengthening Micro-Enterprises for Rural Women - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
48 Páginas. Series Reports, Results and Recommendations of Technical Events A2/JM (IICA) no. 99-06.